Структура флор техногенных территорий Донецкой области - Тохтарь, В.К. (Промышленная ботаника, 2003)
The research of structure of floras formed in various technogenous territories in the Donetsk region: iron and motorways, territories of metallurgical and coke-chemical plants, bread-making factories, ash dumps of the Zuev power station, a waste heap of coal and mercurial dumps has been carried out. The taxonomic and typological analysis of the floras of technogenous territories testifies to their similarity in their taxonomic spectra and ratio of various biotypes in them. Differentiation in formation of some floras is obviously determined by complex action of anthropogenous and natural factors. The degree of these differences depends on compared levels of structure in the floras and raises in the next order: a spectrum of families - a spectrum of sorts - biotypes - specific structure.